Reconhecimento pessoal e verdade no processo penal: uma discussão à luz do Garantismo de Luigi Ferrajoli - ALVES, Luize Cristina de Oliveira (Universidade Federal do Pará, 2023)
The aim of the present research is, through a bibliographic review, establish a relationship between the question of truth in criminal proceedings and the production of proof of recognition of people. The Penal Guarantee of Luigi Ferrajoli was used as the main theoretical foundation and, as a legislative framework, was used the positivation of guarantees brought by the Constitution of the Republic of 1988. The aim was to assess whether personal recognition, as currently provided for in art. 226 of the CPP and in the forms of its pratical realization, meets (or not) the ferrajolian perspective of truth in the process. In this way, it was necessary to demonstrate the importance of the debate about procedural truth and to situate Luigi Ferrajoli’s position on this issue. It was also sought to verify to what extent the legal provision and the daily practice of carrying out this procedure are in line with the scientific production on the subject. It was concluded that there is a discrepancy between the model of recognition of people that we currently have in the Brazilian criminal procedure (in art. 226 of the CPP and in practice) and the minimum guidelines indicated by the psychology of testimony, already adopted by several international legislations. Thus, using the contributions and knowledge of this branch of psycology, especially with regard to the functioning of human memory, it is intended to point out mechanisms embodied in procedural guarantees, that allow greater rational control of the act of recognition in order to satisfy the research for an approximate truth (Ferrajolian conception) in the identifications of authorship.